Appalachian Hikers' Digital Journals: Collective Writing for an Unruly Landscape. Issue 1 (1st March 2022) - McLaughlin, David
Abstract: The Appalachian Trail—a hiking trail in the eastern United States—is for many an icon of the American wilderness experience. It is an unruly landscape, one which is yearly being re-made, re-marked, and "reclaimed" to wilderness. Within its corridor of trees, the Appalachian Trail hides decaying farms bought by forced purchase, ghosts of old cemeteries, and many different paths through the trees. There is a palpable sense of possibility, of constant change, and of what could have been. In this article, drawing on recent research in cultural geography which emphasizes the unsettled and unsettling nature of landscape, I will introduce the potential for new, digital literary-spatial forms made on the Appalachian Trail to write and to enact this unruly landscape.